2018
DOI: 10.5607/en.2018.27.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Underlying Mechanism of Moxibustion in Preventing Cognitive Impairment: A Systematic Review of Animal Studies

Abstract: Cognitive impairment is age-related and manageable only with early diagnosis and prevention. Moxibustion is widely accepted in East Asia as useful for preventing cognitive impairment. This systematic review of animal studies was conducted to verify the efficacy of moxibustion in preventing cognitive impairment and to elucidate the underlying mechanism. Randomized controlled animal trials that established the efficacy of moxibustion in preventing cognitive impairment were included in the analysis. Results of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…30,65 Moxibustion is the application of heat to a part of the body through the burning of dried plant materials near the skin. 71 This study reported a statistically significant reduction in pain with the intervention (MD −2.75, 95% CI −3.64, −1.86). Risk of bias was assessed as being moderate for the included study; however, the number of participants was very low.…”
mentioning
confidence: 69%
“…30,65 Moxibustion is the application of heat to a part of the body through the burning of dried plant materials near the skin. 71 This study reported a statistically significant reduction in pain with the intervention (MD −2.75, 95% CI −3.64, −1.86). Risk of bias was assessed as being moderate for the included study; however, the number of participants was very low.…”
mentioning
confidence: 69%
“…Compared to our previous SR 22 investigating the efficacy of moxibustion in preventing cognitive impairment, this study is more focused on the therapeutic effects of moxibustion. In both SRs, moxibustion treatment improved the behavioral test scores, and suppression of apoptosis and inflammation appeared to be the common mechanism induced by moxibustion.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with acupuncture studies, the therapeutic efficacy of moxibustion for cognitive impairment has not been fully validated. Although a previous study has reported the action of moxibustion in preventing cognitive impairment, 22 information on the overall therapeutic effect of moxibustion was limited, as it was focused on prevention. This SR aimed to evaluate the efficacy of moxibustion in treating cognitive impairment through a meta-analysis of animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cholinesterase inhibitors have limited or no signi cant effects on cognitive function over the short term and may substantially increase adverse effects, based on a meta-analysis of 4 trials (1960 participants)and another meta-analysis of 9 trials (5149 participants).Consequently, cholinesterase inhibitors and memantine are not recommended for MCI treatment and there are currently no FDA-approved medications for MCI [44,45]. We have known a series of studies in men and animals that acupuncture and moxibustion can improve memory on AD or MCI [46][47][48]. Moxibustion could help prevent cognitive impairment, and prevention is currently the only suitable management technique for this disorder [49].…”
Section: Introductionmentioning
confidence: 99%